2014
DOI: 10.1177/1541931214581278
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Task Skill and Team Familiarity on Shared Knowledge and Collective Efficacy

Abstract: In this paper we addressed one aspect of team cognition, namely shared knowledge, and investigated the relationship between shared knowledge and collective efficacy. The task was doubles tennis; participants were 160 adults, for a total of 80 teams. Data was collected via self-report questionnaires. As we had suspected, there was a strong, positive relationship between collective efficacy and shared knowledge (r = .5, p < .05). Using hierarchical regression, we also found that team familiarity was positively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Collective teacher efficacy has a significant and positive impact on knowledge sharing. This is consistent with the results of Reynolds and Blickensderfer [24]. The collective teacher efficacy is the sum of the beliefs of individual teachers about their collective abilities and this assessment of collective abilities affects their course of action and effort in pursuit of goals [17].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Collective teacher efficacy has a significant and positive impact on knowledge sharing. This is consistent with the results of Reynolds and Blickensderfer [24]. The collective teacher efficacy is the sum of the beliefs of individual teachers about their collective abilities and this assessment of collective abilities affects their course of action and effort in pursuit of goals [17].…”
Section: Discussionsupporting
confidence: 91%
“…Scholars have discussed the relationship between individual self-efficacy and knowledge sharing but there are few studies on the relationship between collective efficacy and knowledge sharing. Reynolds and Blickensderfer [24] investigated the data of 160 adults playing tennis in pairs and found that there was a significant positive relationship between collective efficacy and knowledge sharing because team cognition is not simply the sum of the cognitions of individual members, researchers need to further verify the relationship between collective effectiveness and knowledge sharing. Thus, we propose our second research hypothesis as follows:…”
Section: Collective Teacher Efficacy and Knowledge Sharingmentioning
confidence: 99%
See 1 more Smart Citation